Gambaran Faktor yang Mempengaruhi Ibu Tidak Memberikan ASI Eksklusif di Wilayah Kerja Puskesmas Cakru, Kencong - Hiqmatul Faizzah; Dini Kurniawati; Peni Perdani Juliningrum (Pustaka Kesehatan, 2022)
Exclusive breastfeeding is needed due to the low coverage of exclusive breastfeeding. The purpose of this study was to identify the description of maternal factors not to provide exclusive breastfeeding at the Public Health Centre of Cakru Kencong-Jember Regency. The study used a cross-sectional study. This study was conducted on 127 mothers who had infants aged 0-6 months and did not give exclusive breastfeeding with a total sampling technique. Data collection used a questionnaire about knowledge, family support, and formula milk exposure in January - February 2019. The results showed that most respondents had the most factors affecting mothers not to give exclusive breastfeeding, namely low education factors (31.5% ), good knowledge (95,3%), not working or housewives (76.4%), low socio-economic (74.8%), supportive family supports (96.1%), and exposure to formula milk exposed (70.1%) in breastfeeding is not exclusive at the Public Health Centre of Cakru Kencong-Jember. The study illustrated that the factors of education, housewives, socio-economics, and formula milk exposure are very dominant in decreasing the coverage of exclusive breastfeeding so that mothers are reluctant to give breast milk exclusively to infants aged 0-6 months on the grounds that breast milk does not adequately meet their baby's needs.